Can the rebreathing method be applied in the swim flume and swimming pool? - Reer, R.; Schmidt, B.; Ziegler, M.; Braumann, K.-M. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
Spiroergometry in the swim flume as an online method facilitates the simultaneous, reciprocally influencing ifferentiation between physiological (metabolic-cardiopulmonary) and technical-coordinative performance within the framework of performance diagnosis and training control. The aim of the present study was to test if the rebreathing method can be introduced as a valid spirometric measuring system in the swim flume as well as in the swimming pool. For this purpose 32 swimmers performed a standardized step test in the swim flume (first step: 1.10 m/s, increase: 0.09 m/s every 3 minutes, break: 1 minute between each step) with and without mask. While performing the test with mask, the spirometric data were registered in an online manner. During the test without mask, the mask was put on immediately after the end of each exercise step and the spirometric data were registered during the oneminute break (rebreathing method). With reference to the data from extrapolation, applying the exponential regression equation y=ae-bx, it could be demonstrated that the test results with and without mask did not show any substantial differences (1.10 m/s: 2330+/-397 vs. 2183+/-598 ml; 1.19 m/s: 2616+/-441 vs. 2557+/-616 ml; 1.28 m/s: 2927+/-483 vs. 2810+/-470 ml; 1.37 m/s: 3247+/-549 vs. 3195+/-606 ml; 1.46 m/s: 3620+/-533 vs. 3779+/-700 ml). The present data indicate that the rebreathing method may be suitable for employment in the pool. Therefore, the rebreathing method could serve as a link for interpretation of spirometric data ascertained during the afterload phase in the pool and those registered online in the swim flume.